LEARNING TO PREVENT AND BREAK THE CHAIN OF TRANSMISSION OF COVID-19 BY VACCINATE WOMEN, PREGNANT AND BREASTFEEDING MOTHERS THROUGH THE WEBINAR - Bachnas, Muhammad Adrianes; Anggraini, Nutria Widya purna; Sulistyowati, Sri; Yuliantara, Eric Edwin; Prabowo, Wisnu; Nugraha, Gagah B Adi; Firmansyah, Aldi; Prameilita, Dympna (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: The incidence of Covid-19 in women, pregnant, and breastfeeding mothers is still high. Currently, the government is trying to prevent and break the chain of Covid-19 transmission by vaccination. However, knowledge about Covid-19 vaccination is still limited. Therefore, Indonesian Obstetrics and Gynecology Association/Perkumpulan Obstetri dan Ginekologi Indonesia  (POGI) members, as the spearhead of women's health, play an essential role in breaking the chain of transmission by providing knowledge about Covid-19 vaccination.Methods: All member of POGI and Youth POGI in Surakarta was educated by online method via the webinar zoom application. The level of knowledge was evaluated pre and post-webinar by using a questionnaire to see the significance.Result: Analysis of 110 participants with paired t-test obtained an average pretest value of 44.82 while the average post-test value was 57.45, with a significance value of p=0.001 (p<0.05). The results of the analysis with the Chi-square test obtained p = 0.002 (p <0.05) and OR = 23.40.Conclusion: There is an increased understanding of preventing and breaking the chain of transmission of Covid-19 in women, pregnant, and breastfeeding mothers by vaccinating youth POGI and POGI members after webinar and discussion, with a significance value of p=0.001 (p<0.05). Webinars and discussions on preventing and breaking the chain of transmission of Covid-19 to women, pregnant, and breastfeeding mothers with vaccination by researchers provided 23.40 times better understanding than before the webinar and discussions were given.